Evaluation of Xpert MTB/RIF assay in children with presumed pulmonary tuberculosis in Papua New Guinea. (3rd April 2018) - Kasa Tom, Sharon; Welch, Henry; Kilalang, Cornelia; Tefuarani, Nakapi; Vince, John; Lavu, Evelyn; Johnson, Karen; Magaye, Ruth; Duke, Trevor
Abstract: Background: The Gene Xpert MTB/ RIF assay (Xpert) is used for rapid, simultaneous detection of Mycobacterium tuberculosis (MTB) and rifampicin resistance. This study examined the accuracy of Xpert in children with suspected pulmonary tuberculosis (PTB). Methods: Children admitted to Port Moresby General Hospital with suspected PTB were prospectively enrolled between September 2014 and March 2015. They were classified into probable, possible and TB-unlikely groups. Sputum or gastric aspirates were tested by Xpert and smear microscopy; mycobacterial culture was undertaken on a subset. Children were diagnosed with TB on the basis of standard criteria which were used as the primary reference standard. Xpert, smear for acid-fast bacilli (AFB) and the Edwards TB score were compared with the primary reference standard. Results: A total of 93 children ≤14 years with suspected PTB were enrolled; 67 (72%) were classified as probable, 21 (22%) possible and 5 (5.4%) TB-unlikely. Eighty were treated for TB based on the primary reference standard. Xpert was positive in 26/93 (28%) MTB cases overall, including 22/67 (33%) with probable TB and 4/21 (19%) with possible TB. Three (13%) samples identified rifampicin resistance. Xpert confirmed more cases of TB than AFB smear (26 vs 13, p  = 0.019). The sensitivity of Xpert, AFB smear and an Edwards TB score of ≥7 was 31% (25/80), 16% (13/80) and 90% (72/80), respectively, and the specificity was 92% (12/13), 100% (13/13) and 31% (4/13), respectively, when compared with the primary reference standard. Conclusion: Xpert sensitivity is sub-optimal and cannot be relied upon for diagnosing TB, although a positive result is confirmatory. A detailed history and examination, standardised clinical criteria, radiographs and available tests remain the most appropriate way of diagnosing TB in children in resource-limited countries. Xpert helps confirm PTB better than AFB smear, and identifies rifampicin resistance. Practical guidelines should be used to identify children who will benefit from an Xpert assay.